Benzyl N-((S)-2-hydroxy-1-{N `-[(E)-2-methoxybenzylidene]hydrazine-carbonyl}ethyl)carbamate from synchrotron data - Pinheiro, A.C.; De Souza, M.V.N.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
A U-shaped conformation is found in the title compound, C(19)H(21)N(3)O(5), with the benzene rings lying to the same side of the molecule; the dihedral angle between them is 10.83 (16)degrees. The dihedral angle formed between the hydrazinecarbonyl and carbamate residues is 68.42 (13)degrees. The carbonyl groups lie approximately at right angles to each other [O-C center dot center dot center dot C-O pseudo torsion angle of 107.7 (3)degrees], and the conformation about the C12=N3 bond [1.279 (4) angstrom] is E. An intramolecular N(cb)-H center dot center dot center dot O(hy) (cb = carbmate and hy = hydroxy) hydrogen bond occurs, generating an S(6) loop. In the crystal, intermolecular O(h)-H center dot center dot center dot O(ca) (ca = carbonyl) and N(hz)-H center dot center dot center dot O(ca) (hz = hydrazine) hydrogen bonds lead to the formation of a supramolecular chain, two molecules thick, which propagates along the a axis; these are connected by C-H center dot center dot center dot O(ca) contacts.